Indiscriminada emisión de boletas de auxilio en violencia intrafamiliar. - Ramón Ramón, Carolina Elizabeth (2015)
Our scientific research aims to collect the outstanding analysis concerning the ballot for help, and the various factors that favor its indiscriminate issuance, consequences and statistics, fundamentations in a legal and doctrinal judgment on Article 558 of the Penal Code of Integral. Likewise with this analysis we propose determine the effects that the indiscriminate delivery of the ballot for help in family dynamics of women reporting violence against men who would be reported is. This work derives based on the experience gained in the former Commissioners for Women and the Family, and then in the current units of domestic violence, where everyday excessive distress ballots are issued, each accompanied by a different story including a credible and some implausible, but all with the same goal apparent ward off these attacks are physical or psychological. Most women who were granted a ballot of assistance without prior verification of what happened, that women use these ballots gave relief and these have meaning in their lives was unknown, a situation that was difficult to know because there is little follow its legal processes as the family environment. The study begins with an analysis of the theoretical basis that interrelates the family and violence, that is, based on these studies identifies how it was referred to the family from theoretical positions, the emergence of new family structures indicated and refers to studies on domestic violence. We have collected for this work all national and international legislation concerning the protection of women and protection against domestic violence and human rights the same as for legal and doctrinal support our proposal.